Comparing surgical and oncologic outcomes between laparoscopic gastrectomy and open gastrectomy in advanced gastric cancer with serosal invasion: A retrospective study with propensity score matching. Issue 9 (September 2022) - Jeong, Seong-A; Yoo, Moon-Won; Lee, In-Seob; Gong, Chung Sik; Ko, Chang Seok; Jheong, Jin Ho; Lee, Jung-Bok; Kim, Beom-Su
Abstract: Purpose: Laparoscopic gastrectomy (LG) has gradually increased for treating advanced gastric cancer (AGC). However, there is a lack of evidence on oncologic safety for AGC, especially with serosal invasion. This study evaluates the surgical and oncologic outcomes between laparoscopic and open gastrectomy (OG) for gastric cancer with serosal invasion. Methods: We retrospectively reviewed 256 patients who underwent OG and 147 patients who underwent LG for gastric cancer with serosal invasion between August 2005 and December 2017. Finally, 124 patients in the LG group and 124 in the OG group were enrolled according to one-to-one propensity score matching (PSM) analysis. We evaluated surgical and oncological outcomes, including overall survival (OS) and recurrence-free survival (RFS). Results: There were no statistical differences in hospital stay and major complications between the two groups. The retrieved lymph nodes of the LG group were similar to those of OG (40 ± 16.23 vs . 38 ± 14.42, p = 0.306), and it showed a similar operation time compared with the other (164 ± 43.86 vs . 156 ± 37.66, p = 0.063). There was no statistical difference in OS ( p = 0.761) and RFS ( p = 0.121) for survival analysis between the two groups. Conclusion: LG for gastric cancer with serosal invasion is feasible and could be considered as a standard treatment.